Simultaneous bilateral olecranon fracture: a case report and review of the literature - Canton, Gianluca; Roman, Federico; Ghassempour, Dario; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2021)
ABSTRACTBackground and aim of the work: A bilateral fracture of the olecranon is a rare injury, with only few cases reported in the literature.Methods: A single case of bilateral Mayo type II A olecranon fracture in a 88 years old woman is described. A research of all articles regarding simultaneous bilateral olecranon fracture was performed in the PubMed database.Result: The reported case demonstrated good clinical and radiographic results at 5 months follow-up with surgical treatment. The literature search produced other 6 cases in 5 case reports. Except for one case of fatigue fracture that had been treated conservatively, the others received surgical treatment with satisfactory results.Conclusion: Simultaneous bilateral olecranon fracture is very uncommon. Bilateral internal fixation yields good clinical and radiographic results in most cases.